Antibacterial and cytocompatible silver coating for titanium Boston Keratoprosthesis - Gómez, Silvia González; Ginebra, Maria-Pau; Gil, Francisco Javier; Barraquer, Rafael I.; Manero, José María (Frontiers in Bioengineering and Biotechnology, 2024)
The Boston Keratoprosthesis (BKPro) serves as a medical solution for restoring vision in complex cases of corneal blindness. Comprising a front plate made of polymethylmethacrylate (PMMA) and a back plate of titanium (Ti), this device utilizes the beneficial biomaterial properties of Ti. While BKPro demonstrates promising retention rates, infection emerges as a significant concern that impacts its long-term efficacy. However, limited research exists on enhancement of BKPros through intrinsic infection-preventing mechanisms. In this regard, metal ions, especially the well-known Ag+ ions, are a promising alternative to obtain implants with innate antibacterial properties. However, little information is available about the effects of Ag in corneal tissue, especially within human corneal keratocytes (HCKs). In this work, an electrodeposition treatment using a constant pulse is proposed to attach Ag complexes onto rough Ti surfaces, thus providing antibacterial properties without inducing cytotoxicity. Complete physicochemical characterization and ion release studies were carried out with both control and Ag-treated samples. The possible cytotoxic effects in the short and long term were evaluated in vitro with HCKs. Moreover, the antibacterial properties of the silver-treated surfaces were tested against the gram-negative bacterial strain Pseudomonas aeruginosa and the gram-positive strain Staphylococcus epidermidis, that are common contributors to infections in BKPros. Physicochemical characterization confirmed the presence of silver, predominantly in oxide form, with low release of Ag+ ions. Ag-treated surfaces demonstrated no cytotoxicity and promoted long-term proliferation of HCKs. Furthermore, the silver-treated surfaces exhibited a potent antibacterial effect, causing a reduction in bacterial adhesion and evident damage to the bacterial cell walls of P. aeruginosa and S. epidermidis. The low release of Ag+ ions suggested reactive oxygen species (ROS)-mediated oxidative stress imbalance as the bactericidal mechanism of the silver deposits. In conclusion, the proposed electrodeposition technique confers antibacterial protection to the Ti backplate of BKPro, mitigating implant-threatening infections while ensuring non-cytotoxicity within the corneal tissue.